Smart Wireless Sensor Networks (WSNs): A Review on Concepts, Techniques, and Applications - Ali Hassan Sial; Muhammad Shafiq; Zubair Sajid Sial; Saleem Ahmed (Sir Syed University Research Journal of Engineering and Technology, 2025)
In this modern era, Wireless Sensor Networks (WSNs) are considered rapidly evolving areas of computational research that constitute energy consumption, routing algorithms, and location-based sensors with a sole focus on robustness, efficiency, and improved performance metrics. Seemingly, there are a wide variety of applications available in the dimensions of WSNs in terms of application design aspects, the main aim is to enable the functional aspects for a longer time duration. The key element focuses on the way the network is designed and how the survey conducted presents more recent developmental strategies and methods for the WSNs. In this paper, the review work is presented in a distributed and centralized environment. The overall analysis is dedicated to whether an individual or multiple sinks are active, nodes are static or mobile-friendly, and the entire development is based on the recognition of events to identify the sustainability of the network system to be implemented in the real-world environment. The purpose of this research is to focus on the recent contributions and discussions on the real-world application areas in which WSNs can be implemented. Furthermore, the paper highlights a range of open-ended issues, which is a further addition to research in this area.